The tolerogenic peptide hCDR1 immunomodulates cytokine and regulatory molecule gene expression in blood mononuclear cells of primary Sjogren's syndrome patients - Sthoeger, Zev (Clinical immunology (Orlando, Fla.), 2018)
Copyright © 2018 Elsevier Inc. All rights reserved.